THE DEVELOPMENT OF CHARACTER-BASED STUDENTS WORKSHEET FOR SUBDISCUSSION OF PHYLUM MOLLUSCA AT TENTH GRADE OF HIGH SCHOOL - SUMARSONO YULI PRASETYO (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2013)
This research aimed to develop character-based students’ worksheet for subdiscussion of Phylum Mollusca which is feasible theoretically and empirically. This research was developmental research which develop character-based students’ worksheet by 4-D method (without disseminate phase). The result showed that the characters-based students’ worksheet that have been developed was feasible, both theoretically and empirically. The worksheet got good result, because the validation result showed that 93,75%. The worksheet was also good empirically students’ response was 97%. Keywords: Student’s worksheet, Character education, Phylum Mollusca, Biology, Grade